2013
DOI: 10.1371/journal.pntd.0002552
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma cruzi TcSMUG L-surface Mucins Promote Development and Infectivity in the Triatomine Vector Rhodnius prolixus

Abstract: Background TcSMUG L products were recently identified as novel mucin-type glycoconjugates restricted to the surface of insect-dwelling epimastigote forms of Trypanosoma cruzi, the etiological agent of Chagas disease. The remarkable conservation of their predicted mature N-terminal region, which is exposed to the extracellular milieu, suggests that TcSMUG L products may be involved in structural and/or functional aspects of the interaction with the insect vector.Methodology and Principal FindingsHere, we invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 52 publications
(69 reference statements)
2
25
0
Order By: Relevance
“…Each R. prolixus fifth instar had not eaten for about 2 weeks. 66,67 We placed each jar of nymphs under an artificial membrane feeder containing the parasite-blood solution at 37.5°C for about 30 minutes. 68 Control insects consumed blood without parasites.…”
Section: Methodsmentioning
confidence: 99%
“…Each R. prolixus fifth instar had not eaten for about 2 weeks. 66,67 We placed each jar of nymphs under an artificial membrane feeder containing the parasite-blood solution at 37.5°C for about 30 minutes. 68 Control insects consumed blood without parasites.…”
Section: Methodsmentioning
confidence: 99%
“…are also significant public health problems, affecting millions of people every year. These diseases are quite neglected since they are generally related to poverty, with limited therapeutic strategies and highly toxic drugs available [6,7]. Thus, the development of new drugs and strategies to inhibit, control and prevent these diseases is also necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Special attention is given to the interactions of these parasites within the gut and to the effects of the organization of midgut epithelial cells on the parasite development and metacyclogenesis. Gonzalez et al (2013) have shown that the insect vector's permissiveness to T. cruzi depends on the adhesion of the epimastigotes to the perimicrovillar membranes of the midgut to develop.…”
Section: Resultsmentioning
confidence: 99%
“…Because of the lack of a vaccine or an effective treatment for Chagas' disease, vector control is one of the primary methods for preventing this disease. Studying the internal structures of R. Prolixus head is of great importance in vector control (Rembold and Garcia, 1989;Garcia et al, 1984;Gonzalez et al, 2013). organs syntopy and structure of R. prolixus without invading or disrupting them, as shown by Almeida et al (2012aAlmeida et al ( , 2012bAlmeida et al ( , , 2014.…”
Section: Introductionmentioning
confidence: 99%